Phosphorylation of Rhoptry Protein RhopH3 Is Critical for Host Cell Invasion by the Malaria Parasite - Roseleen Ekka (American Society for Microbiology, 2020)
ABSTRACT Merozoites formed after asexual division of the malaria parasite invade the host red blood cells (RBCs), which is critical for initiating malaria infection. The process of invasion involves specialized organelles like micronemes and rhoptries that discharge key proteins involved in interaction with host RBC receptors. RhopH complex comprises at least three proteins, which include RhopH3. RhopH3 is critical for the process of red blood cell (RBC) invasion as well as intraerythrocytic development of human malaria parasite Plasmodium falciparum. It is phosphorylated at serine 804 (S804) in the parasite; however, it is unclear if phosphorylation regulates its function. To address this, a CRISPR-CAS9-based approach was used to mutate S804 to alanine (A) in P. falciparum. Using this phosphomutant (R3_S804A) of RhopH3, we demonstrate that the phosphorylation of S804 is critical for host RBC invasion by the parasite but not for its intraerythrocytic development. Importantly, the phosphorylation of RhopH3 regulates its localization to the rhoptries and discharge from the parasite, which is critical for RBC invasion. We also identified P. falciparum CDPK1 (PfCDPK1) as a possible candidate kinase for RhopH3-S804 phosphorylation and found that it regulates RhopH3 secretion from the parasite. These findings provide novel insights into the role of phosphorylation in rhoptry release and invasion, which is poorly understood. IMPORTANCE Host cell invasion by the malaria parasite is critical for establishing infection in human host and is dependent on discharge of key ligands from organelles like rhoptry and microneme, and these ligands interact with host RBC receptors. In the present study, we demonstrate that phosphorylation of a key rhoptry protein, RhopH3, is critical for host invasion. Phosphorylation regulates its localization to rhoptries and discharge from the parasite.